Kebarangkalian bekerja wanita berkahwin di Malaysia - Abdullah, Norehan; Ismail, Rahmah; Mohd Noor, Zulridah; Ahmad, Fariza (Universiti Kebangsaan Malaysia, 2012)
This study identifies the determinants of labor force participation of Malaysian married women and the issue of child care.Using a cross-section data of a survey done in the states of Selangor and Kedah, this study applied a probit model to explore the determinants of labor force participation of Malaysian married women. Consistent with previous studies, the probit analysis shows that the wage rate and number of children aged 18 years and above have positive significant impact on the probability to work, while husband’s income and number of children aged below six years have significant negative impact on married women’s decision to participate in the labor force.Interestingly, this study suggests that an increase in the costs of childcare significantly affects the labor supply of married Malaysian women.